Answer:
- A"(-1, -2)
- B"(6, 0)
- C"(3, 3)
- (x, y) ⇒ (x+1, y+1)
Explanation:
Translation vectors add, and the addition is commutative and associative.
__
The first translation adds (-1, 2) to the original coordinates. The second translation adds (2, -1) to the original coordinates. The two translations together add ...
(-1, 2) +(2, -1) = (-1+2, 2-1) = (1, 1)
to the original coordinates.
The single rule representing this translation is ...
(x, y) ⇒ (x +1, y +1)
Then the doubly-translated coordinates are ...
A(-2, -3) ⇒ A"(-1, -2)
B(5, -1) ⇒ B"(6, 0)
C(2, 2) ⇒ C"(3, 3)